Speaking together differently to live together differently The promise of the public dialogue movement - Johnson, Susanne 1950- (2018)
The struggle for mutual respect of difference may be the most paradigmatic form of public conflict in the United States and elsewhere today. In recent years, a movement and broad community of practice has burgeoned in the United States and beyond, which brings people together across deep divides to engage in dialogue aimed to reduce conflict and foster mutual understanding. In this article, I introduce the public dialogue movement, and argue that as religious educators we should see ourselves called by the "signs of the times" to widen our praxis of dialogue across divides beyond our historic, robust leadership in interreligious dialogue.